Diosgenin production by immobilized cell - Soegihardjo, C.J.; ., Koensoemardiyah (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
In the last two decade, secondary metabolite production by plant tissue culture in several countries by plant tissue cultures were done by plant suspension culture method, in volumes until several thousand litres. There are many problems occur in the production by cells suspension culture. Some problems could be overcome by choosing suitable media, other could be solving by immobilized cells system. Immobilized cells system is promising method because it has some advantages. The aim of this research is to produce diosgenin from amobilized cells of Costus speciosus Smith. From this result we hope to know about the possibility of using immobilized cells system as alternative method for producing diosgenin. The main substance of this research is the mature seeds of C. speciosus (fam. Zingiberaceae) grown in RT-0 semisolid medium. The seedlings become explant for initiating calli by growing in RT 1 semisolid medium. After some passages of subculturing the calli, initiation of cell suspension culture was carried out by growing friable calli on RT-0,1 liquid medium. After some passages of subculturing cell suspesion culture, the biomass were collected and trapped in calcium alginate beads. The type of bioreactor used was shaking-flask. The immobilized cells were treated in RT liquid medium added with 0.1 ppm 2,4-D (RTA), second group in RTA added with 0.2% yeast extract (RTB), and the third group in RTA added with 0.2% yeast extract and 0.05% cholesterol. From this investigation can be concluded that diosgenin production in immobilized cell system treated with elicitor and precursor was increased four to ten times as great as its production without any addition for fine cells and for coarse cells about eight and three times fold. Key words: Costus speciosus cells, diosgenin production, immobilized cells, elicitation, precursor, spectro-densitometri.